Analisa Kebutuhan Kompetensi Lulusan PPIC terhadap Perusahaan Penerbangan - Endang Sugih Arti; Hendro Widiarto; Ika Endrawijaya; Nawang Kalbuana; Dian Anggraini Purwaningtyas (Journal on Education, 2024)
Higher education as a producer of quality human resources must be oriented to the competencies needed by the world of work because the percentage of unemployment continues to increase. This study aims to examine the level of suitability or relevance and the gap between the abilities (skills) of graduates of the Indonesian Aviation Polytechnic Curug to the abilities needed in the industrial sector. The data collection method uses questionnaires through google forms and tracer study approaches involving alumni of the Indonesian Aviation Polytechnic Curug from various study programs. The results of this study obtained factors that are obstacles in careers and the reason for the gap that occurs between the knowledge and competencies of alumni to the needs of the world of work, this is one of the efforts to overcome unemployment problems and develop a curriculum that can affect the quality of PPIC graduates in collaboration with stakeholders.